The effectiveness of social media influences and celebrity endorser on the Smartphone users’ brand choice behavior - Kalam, Abul (Curtin University, 2023)
Based on the data of Malaysian consumers, this study reveals that SMI and CE are the prevailing marketing strategies for swaying Smartphone users’ BCB. The study refines a meaningful and deep insight into the unexplored areas of marketing research to bridge the study gaps and unveil the pavement for promoting brands. This research sheds new light on divulging uncharted proposed relationships that may concentrate the focus of academics and practitioners.